2021
DOI: 10.1002/adma.202008140
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Assembly of Flexible Ultrathin All‐in‐One Zinc‐Ion Batteries with Highly Stretchable, Editable, and Customizable Functions

Abstract: Aqueous zinc‐ion batteries (ZIBs) are considered to be a promising candidate for flexible energy storage devices due to their high safety and low cost. However, the scalable assembly of flexible ZIBs is still a challenge. Here, a scalable assembly strategy is developed to fabricate flexible ZIBs with an ultrathin all‐in‐one structure by combining blade coating with a rolling assembly process. Such a unique all‐in‐one integrated structure can effectively avoid the relative displacement or detachment between nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
123
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 60 publications
0
123
0
Order By: Relevance
“…Polyaniline (PANI), probably the most studied conducting polymer, is a promising cathode material for aqueous zinc batteries, 1–7 mainly due to its good electrical conductivity, high electrochemical reactivity/reversibility, and low cost. 8–22 Depending on the oxidation degree, three forms of PANI have been recognized: reduction state (leucoemeraldine), half oxidation state (emeraldine), and oxidation state (pernigraniline) (Scheme 1). 23 The redox transitions of leucoemeraldine/emeraldine and emeraldine/pernigraniline result in the two typical redox couples of PANI during electrochemical applications.…”
mentioning
confidence: 99%
“…Polyaniline (PANI), probably the most studied conducting polymer, is a promising cathode material for aqueous zinc batteries, 1–7 mainly due to its good electrical conductivity, high electrochemical reactivity/reversibility, and low cost. 8–22 Depending on the oxidation degree, three forms of PANI have been recognized: reduction state (leucoemeraldine), half oxidation state (emeraldine), and oxidation state (pernigraniline) (Scheme 1). 23 The redox transitions of leucoemeraldine/emeraldine and emeraldine/pernigraniline result in the two typical redox couples of PANI during electrochemical applications.…”
mentioning
confidence: 99%
“…One advantage of kirigami-shaped batteries is their capability of maintaining planar geometries, which make them ready to be integrated with other wearable electronics compared to other mountainous structures. For example, Yao et al (2021) have demonstrated editable and cuttable polyaniline-Zn batteries through different editing programs as a stretchable honeycomblike structure, which could deliver stable electrochemical performance even enduring the tensile strain of up to 400% (Figures 2G,H). In addition, the stretchable Zn-air battery was also demonstrated by the kirigami-cutting strategy, obtaining a 160% stretchable serpentine-shaped battery (Qu et al, 2020) (Figure 2I), where stretchable Zn-air battery can deliver 11.5 Wh L −1 and the performance was stable even subjected to 100% deformation with slight variation of the output voltage compared to the initial state.…”
Section: Structural Designs For Stretchable Zn-based Batteriesmentioning
confidence: 99%
“…(G) Kirigami strategies to obtain Zn-polyaniline batteries with 400% stretchability. (H) The stable capacity retention under different tensile strain values (reproduced fromYao et al (2021)). (I) Kirigami strategies to realize Zn-air batteries with 100% stretchability to power a fan (reproduced fromQu et al (2020)).…”
mentioning
confidence: 99%
“…Note that, when fabricating flexible ZIBs, conventional aqueous electrolytes are amorphous and cannot effectively segregate the electrodes to prevent short circuits under stretching or bending (20). As a result, gel electrolytes that consist of a polymer host and a corresponding aqueous electrolyte have been widely used in flexible ZIBs (21,22). According to Hofmeister's effect, SO 4 2− has a strong ability to precipitate commonly used polymer hosts; therefore, ZnSO 4 /MnSO 4 -based gel electrolytes are challenging to fabricate (23).…”
Section: Introductionmentioning
confidence: 99%